A Sharia-Based Digital Farming Platform: Integrating Digital Technology for Efficient Zakat Distribution in Agriculture - Masnur Putra Halilintar; Aulia Istiana Hidayat; Amirkhan Pashayev; Vicente Pironti (Mabadi Iqtishad Al Islami, 2026)
This study contributes to the advancement of Islamic social finance discourse by developing a conceptual framework for a digitally integrated zakat governance model within the agricultural sector. The study addresses a critical gap between productive zakat practices and the emerging landscape of digital agricultural transformation. While previous research has largely focused on the redistributive function of zakat as a mechanism for poverty alleviation, limited scholarly attention has been directed toward its potential transformation into a technology-enabled and productivity-oriented instrument that supports sustainable development objectives. Employing a qualitative research approach through content analysis, this study synthesizes interdisciplinary perspectives from Islamic economics, zakat governance, agricultural technology innovation, and digital sustainability studies. The study proposes a Digital Farming Zakat Platform framework consisting of five interconnected dimensions: geospatial-based beneficiary identification, smart farming empowerment, sharia-compliant financial mechanisms, agricultural market integration, and data-driven monitoring systems.